Scalping Surgery – Dermatologic Indications beyond Curative Primary Skin Cancer Surgery - Wollina, Uwe (Open Access Maced J Med Sci, 2017)
Skin tumours are among the most frequent tumour types of mankind. In the case of large tumours, field cancerization, or satellitosis scalping surgery is a possible option. The procedure can also be used in a palliative setting with tumour debulking. Less common indications are multiple benign tumours of the scalp and chronic inflammatory scalp dermatoses not responding to medical treatment. We present a case series and discuss surgical modalities beyond curative surgery of primary skin cancer.